Adolescent Psychiatry. A Contemporary Perspective for Health Professionals - Merrick, Joav; Sher, Leo (De Gruyter, 2021)
Psychiatric disorders in adolescents are an important social problem relevant to almost all healthcare professionals. The prevalence of mood, anxiety, substance use and other psychiatric disorders among adolescents is high. However, medical professionals are not sufficiently trained about adolescent psychiatric disorders. Primary care providers correctly identify less than a fourth of youth with a depressive or anxiety disorder and many clinicians underestimate the importance of the problem of adolescent psychiatric illnesses and suicidal behavior. Multiple clinical, neurobiological, cultural and legal aspects of psychiatric disorders in adolescents are discussed in this book.